A review of the genus Saccharicoccus Ferris, 1950 (Hemiptera: Coccomorpha: Pseudococcidae) in China, with description of a new species - Zhang, Jiang-Tao; Wu, Bo-Wen; Wu, San-An (Zootaxa, 2018)
The mealybug genus Saccharicoccus Ferris includes three species: S. isfarensis (Borchsenius, 1949), S. sacchari (Cockerell, 1895) and a new species, S. chinensis Zhang, Wu & Wu sp. n. The new species, collected on Miscanthus sp. (Poaceae) and other poaceous weeds in China, is described and illustrated, and molecular analyses based on the mitochondrial gene cytochrome c oxidase subunit I (COI) are provided. Additional data on the distribution and host-plants of each species are given, and a key to the adult females of Saccharicoccus species is provided.